Effective Cooperative Haptic Interaction over the Internet - Glencross, Mashhuda; Jay, Caroline; Feasel, Jeff; Kohli, Luv; Whitton, Mary; Hubbold, Roger (2007 IEEE Virtual Reality Conference, 2007)
We present a system that enables, for the first time, effective transatlantic cooperative haptic manipulation of objects whose motion is computed using a physically-based model. We propose a technique for maintaining synchrony between simulations in a peer-to-peer system, while providing responsive direct manipulation for all users. The effectiveness of this approach is determined through extensive user trials involving concurrent haptic manipulation of a shared object. A CAD assembly task, using physically-based motion simulation and haptic feedback, was carried out between the USA and the UK with network latencies in the order of 120ms. We compare the effects of latency on synchrony between peers over the Internet with a low latency (0.5ms) local area network. Both quantitatively and qualitatively, when using our technique, the performance achieved over the Internet is comparable to that on a LAN. As such, this technique constitutes a significant step forward for distributed haptic collaboration